UPAYA PENINGKATAN MOTIVASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN ALAT PERAGA DI KELAS III SD ISLAM DATOK SULAIMAN PALOPO - Alni, Alni (Pedagogik Journal of Islamic Elementary School, 2019)
This study aims to find out that there is an increase in the use of teaching aids so that they are motivated to study in Grade III Islamic Elementary School Datok Sulaiman Palopo, To find out student learning motivation can be improved by using teaching aids in class III Islamic Elementary School Datok Sulaiman Palopo. (PTK) which consists ofB two cycles each cycle carried out 3 meetings with the stages of planning, implementation, observation and reflection. The subjects of this study were Grade III Islamic SD Datok Sulaiman Palopo students in the odd semester of the 2018/2019 academic year with 28 students. Sources of data used in this study are primary data and secondary data, data collection techniques in this study are interviews, observation, questionnaires and documentation. data obtained shows that the average value in class III before the use of props in prasiklus 53.39. In the first cycle researchers have used teaching aids and the results of the average student scores are 80.53, but in this learning there are still a number of students who have not been maximal and researchers plan to make improvements and continue to cycle II. Then the average student score reaches 89.82. Based on completeness criteria (KKM) in mathematics subjects have achieved results and researchers ended this study until the second cycle.